Metabonomic Profile and Signaling Pathway Prediction of Depression-Associated Suicidal Behavior - Liu, Song (Frontiers in Psychiatry, 2020)
Suicide is the most severe consequence of depression that has become a leading cause of disability and global disease burdens. Recent evidences indicate a central role of small molecules in the pathogenesis of depression and associated suicidal behaviors. However, there lacks a systemic exploration of small molecules in the development of depression-associated suicide, and it remains unclear how they affect individual’s behavior. To compare the metabonomic profiles between drug-naïve patients with depression-associated suicidal behaviors and healthy individuals, we conducted a systemic search of studies for metabolic characteristics in depression-associated suicidal behavior within databases. Manual data curation, statistical analysis and integration were performed in Excel. We further performed an enrichment analysis for signaling pathway prediction using Reactome Pathway Analysis tool. We have identified 17 metabolites that expressed differently between drug-naïve patients with depression-associated suicidal behaviors and healthy controls. We have integrated these metabolites into biological signaling pathways and provided a visualized signaling network in depressed suicidal patients. We have revealed that “transport of small molecules”, “disease”, “metabolism” and “metabolism of proteins” were the most relevant signaling sections, among which “transport of inorganic cations/ anions and amino acids/ oligopeptides”, “SLC-mediated transmembrane transport” and “metabolism of amino acids and derivatives” should be further studied to elucidate their potential pathogenic mechanism in the development of depression and associated suicidal behavior. In conclusion, our findings of these 17 metabolites and associated signaling pathways could provide an insight into the molecular pathogenesis of depression-associated suicidal behavior and potential targets for new drug inventions.